2005
DOI: 10.2337/diabetes.54.8.2360
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning the Diabetic Heart

Abstract: Conflicting evidence exists whether diabetic myocardium can be protected by ischemic preconditioning (IPC). The phosphatidylinositol 3-kinase (PI3K)-Akt pathway is important in IPC. However, components of this cascade have been found to be defective in diabetes. We hypothesize that IPC in diabetic hearts depends on intact signaling through the PI3K-Akt pathway to reduce myocardial injury. Isolated perfused Wistar (normal) and Goto-Kakizaki (diabetic) rat hearts were subjected to 1) 35 min of regional ischemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
229
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(240 citation statements)
references
References 38 publications
7
229
0
4
Order By: Relevance
“…Considerable evidence indicates that hypercholesterolemia abrogates both early [20] and late PC [21,22], although the effects on early PC remain controversial [23]. In addition, it appears that early and late PC are either attenuated or absent in the presence of diabetes [24][25][26]. No information is available regarding the impact of hypertension on PC.…”
Section: Cox-2 Involvement In Pcmentioning
confidence: 99%
“…Considerable evidence indicates that hypercholesterolemia abrogates both early [20] and late PC [21,22], although the effects on early PC remain controversial [23]. In addition, it appears that early and late PC are either attenuated or absent in the presence of diabetes [24][25][26]. No information is available regarding the impact of hypertension on PC.…”
Section: Cox-2 Involvement In Pcmentioning
confidence: 99%
“…Multiple signalling proteins/cascades are dysregulated in the diabetic heart, including extracellular signal-regulated kinase 1 (ERK1), signal transducer and activator of transcription 3 (STAT3) and AKT (a key downstream target of PI3K) [4,[16][17][18][19]. A critical step in developing better therapeutics is to understand which signalling events represent key mechanisms in the development of cardiomyopathy in a setting of hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…In our present study, both IPost and RVP-induced postconditioning nonsignificantly enhanced Akt phosphorylation without affecting ERK1/2 and STAT3 at the beginning of reperfusion. Although several studies showed increased phosphorylation of Akt and/or ERK due to IPost (Tsang et al, 2004;Yang et al, …”
Section: Figurementioning
confidence: 99%